Quantum Menace in Physics Education - Alizoti, Alion (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
This paper discusses the introduction of quantum ideas in general physics and education. Considering the fragile environment of physics education, the paper suggests three possible ways to help teaching and learning of quantum physics, (1) quantum metrics (2) simple experiments demonstrating quantum quantities (3) fractal and quantum analogies between worlds. From this perspective, this paper is also meant to be a test indicator of quantum popularity in physics and education.